The Disincarnate Text: Ritual Poetics in Herbert, Paul, Williams, and Levinas. (June 2017) - Smith, Matthew
This Introduction to a special issue on "The Sacramental Text Reconsidered" provides a brief genealogy of the practice of describing texts, performances, and poetics as sacramental, eucharistic, and incarnational. It also offers a critique and clarification of such reading practices by differentiating between the real divine presence theologically understood to dwell in a proper sacrament and the "disincarnation" enacted by sacramentally laden literary texts and performances. Drawing on the writings of Emmanuel Levinas, Rowan Williams, and St. Paul, I demonstrate the disincarnate as a poetic of ritual and oblation in an extended reading of Herbert's poetry.